1992
DOI: 10.1017/s0022112092002489
|View full text |Cite
|
Sign up to set email alerts
|

Instabilities of three-dimensional viscous falling films

Abstract: A long-wave evolution equation is used to study a falling film on a vertical plate. For certain wavenumbers there exists a two-dimensional strongly nonlinear permanent wave. A new secondary instability is identified in which the three-dimensional disturbance is spatially synchronous with the two-dimensional wave. The instability grows for sufficiently small cross-stream wavenumbers and does not require a threshold amplitude; the two-dimensional wave is always unstable. In addition, the nonlinear evolution of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(52 citation statements)
references
References 15 publications
3
49
0
Order By: Relevance
“…Suslov (2006) developed a more complicated algorithm to compute the absolute-convective stability boundary in the given parameter space. Joo & Davis (1992) analysed instabilities in a falling film using Benney's long-wave evolution equation, and confirmed that the instability is of the convective type. A detailed analysis of the linear stability characteristics of a falling film is given in Kalliadasis et al (2012).…”
Section: Introductionmentioning
confidence: 79%
“…Suslov (2006) developed a more complicated algorithm to compute the absolute-convective stability boundary in the given parameter space. Joo & Davis (1992) analysed instabilities in a falling film using Benney's long-wave evolution equation, and confirmed that the instability is of the convective type. A detailed analysis of the linear stability characteristics of a falling film is given in Kalliadasis et al (2012).…”
Section: Introductionmentioning
confidence: 79%
“…The instability evolves into a nonlinear wavetrain and for heated substrates may lead to film rupture [15]. Transverse instabilities may also be present, leading at long times to a pattern of rivulets with a characteristic transverse wavenumber [16,17]. A recent overview of long wave evolution equations for thin films can be found in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Joo and Davis [21] also studied the 3D behaviour of such pure hydrodynamic instabilities. They found that for perturbations in the stream-wise direction the spanwise direction is always unstable and its growth is slow and grows with the Re number.…”
Section: Hydrodynamic Instabilitymentioning
confidence: 99%